ANALISIS ALGORITMA MONTE CARLO UNTUK MEMPREDIKSI KEUNTUNGAN PEMBANGUNAN APARTEMEN MENGGUNAKAN SCRUM FRAMEWORK - Welliam Ali; Syaeful Anas Aklani (BETRIK, 2022)
This study aims to predict profits in apartment projects. This research was made using the Scrum framework in making AI applications and predicting the benefits of using Monte Carlo. Besides that, making AI applications uses PHP and Xampp to make AI. This study uses qualitative methods to 5 people at different developers. The findings of this study indicate that the results on the analysis of ai applications on the benefits of apartment projects are in accordance with the results on the benefits of projects in the field. The model used by the author is Scrum to help authors complete work one by one quickly and can be recognized in doing Scrum. Scrum is divided into 3 namely Product Owner, Development Team and Scrum Master. Where the Scrum Master is in charge of ensuring the sprint goes well and the Development Team and Product Owner to analyze and design applications. The findings of this study are useful for developers to predict profits in apartment projects to be built.